Exploring the acceptability and attitude toward mobile health applications to aid self-management for people with type 2 diabetes mellitus in Saudi Arabia: A descriptive cross-sectional study - Amani Khardali (PLoS ONE, 2025)
Background The prevalence of Type II diabetes mellitus (T2DM) is increasing, leading to a need for more sustainable and patient-centered solutions. The marketplace for mobile health (mHealth) applications (apps) that aid self-management of chronic diseases, such as T2DM, is growing. However, attitudes toward and acceptance of such technology in Saudi Arabia remain limited, particularly regarding preferences and needs. Therefore, understanding the acceptance and attitude toward using mHealth apps and preferred features is essential for planning appropriate methods and strategies to encourage usage among people with T2DM. This study aimed to determine the acceptance of and attitudes toward mHealth apps for self-management among people with T2DM in Saudi Arabia. It also seeks to understand the features that people with T2DM need and prefer regarding the mHealth apps. Methods A cross-sectional study using a structured self-administered questionnaire was conducted on people with T2DM living in Saudi Arabia. Data were analyzed using descriptive and inferential statistics to examine acceptance, perspectives, and attitudes toward using mHealth apps. Results A total of 424 individuals with T2DM completed the study questionnaire; among them, 92.5% owned smartphones, and 12.3% had previously used mHealth apps. Almost all respondents (98.1%) expressed willingness to use apps for self-managing T2DM. Medication reminders (78.3%) and diet management (69.8%) were the highest-ranked features of the mHealth app for T2DM self-management. Additionally, willingness to use apps for T2DM self-management was positively associated with education level and the number of medications taken daily (P = 0.002 and P = 0.04, respectively). Conclusion Overall, using a mHealth app appears to be an acceptable approach to aid the self-management of T2DM in Saudi Arabia, especially among the younger population. The features most required for future mHealth apps were identified, which could aid the design, acceptability, and usage of such apps.